Robert Bonfil, Oded Irshai, Guy G. Stroumsa, and Rina Talgam, Eds. Jews in Byzantium: Dialectics of Minority and Majority Cultures - Tonias, Demetrios E. (Studies in Christian-Jewish Relations, 2014)
No abstract is available.